Is this true or fake news? A conceptual fake news identification model - Chin, Christie Pei-Yee; Suaini Sura; Tan, Soo Fun; Lai, Po Hung; Kwan, Sharon Sam Mee (e-VIBS, Faculty of Science and Natural Resources, 2021)
Over the years, fake news has become unprecedently omnipresent within our society. As social media (SM) become significant channel for disseminating the latest news, its nature also makes the platform an ideal venue for spreading fake stories. The menace of fake news can influence people's beliefs, attitudes, and behaviour by its ubiquity and has a detrimental impact on society. Due to the risks of fake news, research on combatting fake news has gained attention. Despite there were many plausible interventions to combat the spread of fake news, false stories tend to spread faster than accurate stories because of people. Hence, this paper provides a deeper understanding of the fake news presentation on social media from a theoretical lens of information foraging. This study contributes to the growing literature on fake news by developing a conceptual model to identify fake news on social media.